Análisis del comportamiento de las industrias culturales en Colombia bajo el marco de las políticas gubernamentales (2018)
The culture contributes about 3% of the gross domestic product to the economy of the country according to the WIPO8 (World Organization of Intellectual Property), this percentage reflects the importance of the cultural industries in the economic field. According to some analysts, the cultural or creative industries, as they are also known, are characterized by their high intellectual content, reflecting an accelerated growth after the financial crisis of 2008, since every day there is a large amount of content that travels in the different platforms promoting cultural and creative content.